Development and validation of a nomogram model for the prediction of 4L lymph node metastasis in thoracic esophageal squamous cell carcinoma - Xu, Lei; Guo, Jia; Qi, Shu; Xie, Hou-nai; Wei, Xiu-feng; Yu, Yong-kui; Cao, Ping; Zhang, Rui-xiang; Chen, Xian-kai; Li, Yin (Frontiers in Oncology, 2022)
Objectives: The left tracheobronchial (4L) lymph nodes (LN) are considered as regional LNs for esophageal squamous cell carcinoma (ESCC), but there is a controversy about routine prophylactic 4L LN dissection for all resectable ESCC. This study aimed to develop a nomogram for preoperative prediction of station 4L lymph node metastases (LNM). Methods: A total of 522 EC patients in the training cohort and 370 in the external validation cohort were included. The prognostic impact of station 4L LNM was evaluated, and multivariable logistic regression analyses were performed to identify independent risk factors of station 4L LNM. A nomogram model was developed on basis of multivariable logistic regression analysis. Model performance was evaluated in both cohorts in terms of calibration, discrimination and clinical usefulness. Results: The incidence of station 4L LNM was 7.9% (41/522) in the training cohort. Patients with station 4L LNM exhibited a poorer 5-year overall survival rate than those without (43.2% vs. 71.6%, p<0.001). In multivariate logistic regression analyses, six variables were confirmed as independent 4L LNM risk factors: sex (p=0.039), depth of invasion (p=0.002), tumor differentiation (p=0.016), short axis of largest 4L LN (p=0.001), 4L conglomeration (p=0.006) and 4L necrosis (p=0.002). A nomogram model, contained six independent risk factors, demonstrated a good performance, with the area under the curve (AUC) of 0.921 (95%CI: 0.878-0.964) in the training cohorts and 0.892 (95%CI:0.830-0.954) in the validation cohorts. The calibration curve showed a good agreement on the presence of station 4L LNM between the risk estimation according to the model and histopathologic results on surgical specimens. The Hosmer-Lemeshow test demonstrated a nonsignificant statistic (p=0.691 and 0.897) in the training cohorts and the validation cohorts, which indicated no departure from perfect fit. Decision curve analysis indicated that the model had better diagnostic power for 4L LNM than the traditional LNs size criteria. Conclusions: This model integrated available clinical and radiological risk factors, facilitating precise prediction of 4L LNM in patients with ESCC and aiding in personalized therapeutic decision-making for the need for routine prophylactic 4L lymphadenectomy.